Concentration of heavy metals in street dust and surface soils in urban and peri-urban regions in the Kuala Lumpur metropolitan area - Ismail, Ahmad; Hanapiah, Munirah; Zulkifli, Syaizwan Zahmir; Omar, Hishamuddin; Kamarudin, Nur Amiera (Universiti Putra Malaysia Press, 2019)
The present study aims to determine the level of heavy metals in surface soils and street dust from selected urban and peri-urban locations in the metropolitan city of Kuala Lumpur. Samples were collected from 15 different locations, where Kuala Lumpur City Centre (KLCC) served as the centre point while other locations were located at specific distances from the centre. Surface soils and street dust were collected to detect the level of contamination based on five elements (Zn, Cu, Pb, Cd and Fe). Results indicated that the metal distribution displayed a descending trend as follows: [Fe] > [Zn] > [Pb] > [Cu] > [Cd] and [Fe] > [Zn] > [Cu] > [Pb] > [Cd] in the surface soil and street dust samples, respectively. Geoaccumulation index (Igeo), contamination factor (CF) and pollution load index (PLI) were calculated. Based on the Igeo index, Fe in both samples was found to cause no pollution in all study sites. In surface soils, CF showed all sites were contaminated with Cd in both soil and street dust. In conclusion, the soil sample was polluted with metals while no pollution was found in the street dust in all sites sampled. Further intensive studies are recommended in order to determine other factors which may cause contamination.